Comparison of Antimicrobial Resistance Detected in Environmental and Clinical Isolates from Historical Data for the US. (13th April 2020) - Hua, Megan; Huang, William; Chen, Albert; Rehmet, Michael; Jin, Cade; Huang, Zuyi
Abstract : Antimicrobial resistance (AMR) has become an urgent public health issue, as pathogens are becoming increasingly resistant to commonly used antimicrobials. While AMR isolate data are available in the NCBI Pathogen Detection Isolates Browser (NPDIB) database, few researches have been performed to compare antimicrobial resistance detected in environmental and clinical isolates. To address this, this work conducted the first multivariate statistical analysis of antimicrobial-resistance pathogens detected in NPDIB clinical and environmental isolates for the US from 2013 to 2018. The highly occurring AMR genes and pathogens were identified for both clinical and environmental settings, and the historical profiles of those genes and pathogens were then compared for the two settings. It was found that Salmonella enterica and E. coli and Shigella were the highly occurring AMR pathogens for both settings. Additionally, the genes fosA, oqxB, ble, floR, fosA7, mcr-9.1, aadA1, aadA2, ant(2")-Ia, aph(3")-Ib, aph(3')-Ia, aph(6)-Id, blaTEM-1, qacEdelta1, sul1, sul2, tet(A), and tet(B) were mostly detected for both clinical and environmental settings. Ampicillin, ceftriaxone, gentamicin, tetracycline, and cefoxitin were the antimicrobials which got the most resistance in both settings. The historical profiles of these genes, pathogens, and antimicrobials indicated that higher occurrence frequencies generally took place earlier in the environmental setting than in the clinical setting.